Nikki Haley's Lessons from the New South - Fenimore, Wanda Little (Lexington Books, 2023)
In Nikki Haley's Lessons from the New South, Wanda Little Fenimore traces the resurrection of the phrase “New South” with South Carolina’s former governor, Nikki Haley. Through analyzing speeches, Fenimore demonstrates how politicians use historical terms in new ways that obscure their roots but remain oppressive in the twenty-first century. This book reveals how Nikki Haley manufactured her “New South” as progressive, and forward-thinking, yet the term functions as a form of inferential racism, ultimately, reproducing traditional conservatism rooted in white supremacy. Scholars of rhetoric, communication, political science, and women’s studies will find this book of particular interest.